Pengaruh Senam Kaki terhadap Penurunan Skor Neuropati dan Kadar Gula Darah pada Pasien DM Tipe 2 di Persadia RS. TK. II. Dustira Cimahi - Rita Fitri Yulita; Agung Waluyo; Rohman Azzam (Journal of Telenursing (JOTING), 2019)
This study aims to determine the effect of foot exercise on the reduction of neuropathy scores and blood sugar levels in type 2 DM patients. This study used a quasi experimental design with a pretest-posttest control group design approach. The results of the study in the intervention group there was a significant decrease in neuropathy scores and blood sugar levels (p = 0.001). While in the control group there was no significant decrease in neuropathy scores (p = 0.069) and blood sugar levels (p = 0.184). Based on the results of the Mann-Withney test, it showed that there was a significant difference in decreasing neuropathy scores and blood sugar levels between the intervention group and the control group (p = 0.003; p = 0.042). In conclusion, patients with type 2 diabetes mellitus who were given foot exercises experienced a decrease in neuropathy scores and blood sugar levels. Keywords: Type 2 DM, MNSI Instrument, Blood Sugar Levels, Foot Exercise, Neuropathy Score